Crypt and Villus Transcriptomic Responses in Mouse Small Intestine Following Oral Exposure to Hexavalent Chromium. (22nd December 2021) - Chappell, Grace A; Wolf, Jeffrey C; Thompson, Chad M
Abstract: Oral exposure to hexavalent chromium (Cr(VI)) induces tumors in the mouse duodenum. Previous microarray-based transcriptomic analyses of homogenized mouse duodenal tissue have demonstrated Cr(VI)-induced alterations in various cellular pathways and processes. However, X-ray fluorescence microscopy indicates that chromium localizes primarily to the duodenal villi following exposure to Cr(VI), suggesting that previous transcriptomic analyses of homogenized tissue provide an incomplete picture of transcriptomic responses in the duodenum. Herein, transcriptomic analyses were conducted separately on crypt and villus tissue from formalin-fixed paraffin-embedded transverse duodenal sections from the same study in which microarray-based analyses were previously conducted. A total of 28 groups (7 doses × 2 timepoints × 2 tissue compartments) were analyzed for differential gene expression, dose-response, and gene set enrichment. Tissue compartment isolation was confirmed by differences in expression of typical markers of crypt and villus compartments. Fewer than 21 genes were altered in the crypt compartment of mice exposed to 0.1-5 ppm Cr(VI) for 7 or 90 days, which increased to hundreds or thousands of genes at ≥20 ppm Cr(VI). Consistent with histological evidence for crypt proliferation, a significant, dose-dependent increase in genes that regulate mitotic cell cycle was prominent in the crypt, while subtle in the villus, when compared with samples from time-matched controls. Minimal transcriptomic evidence of DNA damage response in either the crypts or the villi is consistent with published in vivo genotoxicity data. These results are also discussed in the context of modes of action that have been proposed for Cr(VI)-induced small intestine tumors in mice.